Exploring the Needs and Concerns of Women with Early Breast Cancer during Chemotherapy: Valued Outcomes during a Course of Traditional Acupuncture. (2nd September 2013) - Price, S.; Long, A. F.; Godfrey, M.
Abstract : Women diagnosed with breast cancer experience symptom clusters in addition to existential issues from a life-threatening diagnosis during chemotherapy. A complementary therapy, such as traditional acupuncture (TA) with its whole-person orientation, may help to modify these effects, alongside inducing other patient benefits. Exploring the needs and concerns of women and perceived benefits of TA would add to knowledge about its integrative treatment potential. Methods . A longitudinal qualitative study recruited fourteen women to receive up to ten sessions of TA during chemotherapy. They were interviewed before, during, and after chemotherapy. Two practitioners of TA delivered treatment and were interviewed before and after the study, and kept treatment logs and diaries. Interviews were recorded and transcribed, and the data were analysed using grounded theory. Findings . Both broad and specific benefits were reported by the women; a highly valued outcome was enabling coping through the alleviation of symptoms and increased well-being. Practitioners dealt with the presented symptom clusters facilitating outcome patterns, including and beyond individual symptom changes. Further research on TA as a flexible intervention able to respond to the changing needs and concerns of woman during chemotherapy along with the measure of such outcome patterns is warranted.